Defining the flexibility window in ordered aluminosilicate zeolites. Issue 9 (27th September 2017) - Wells, Stephen A.; Leung, Ka Ming; Edwards, Peter P.; Tucker, Matt G.; Sartbaeva, Asel
Abstract : The flexibility window in zeolites was originally identified using geometric simulation as a hypothetical property of SiO2 systems. The existence of the flexibility window in hypothetical structures may help us to identify those we might be able to synthesize in the future. We have previously found that the flexibility window in silicates is connected to phase transitions under pressure, structure amorphization and other physical behaviours and phenomena. We here extend the concept to ordered aluminosilicate systems using softer 'bar' constraints that permit additional flexibility around aluminium centres. Our experimental investigation of pressure-induced amorphization in sodalites is consistent with the results of our modelling. The softer constraints allow us to identify a flexibility window in the anomalous case of goosecreekite.